Percepção do consumo de copos plásticos por universitários - D'Agostin, Andressa (2019)
Waste prevention, especially single-use plastic, is currently a critical issue, and this thesis aims to provide a more nuanced view by examining the determinants of individual behaviour when deciding to use disposable plastic cups. Our research has two main aims: (ii) to examine constructs from psychology theories and emotions behind students’ motivation and barriers to pro-environmental behavior regarding the use of disposable plastic cups; and (ii) to assess students’ perception of different pieces of advertising which aim at promoting pro-environmental behaviour using distinct emotional appeals. In order to reach our first goal, we assessed the answers of 502 students collected through survey questionnaire, by employing descriptive statistics. Results show that concern, awareness of negative consequences, negative emotions, as well as feeling rewarded, are vital to encourage pro-environmental behaviour, namely prevent plastic cups use, although subjective norms were not significant to this process. The second aim involved exposing 96 students to the proposed pieces of advertising, then analyzing data through descriptive statistics and variance analysis. Results show that concern is the most appealing and affecting to most students, corroborating to our findings in the first study. In addition, age and area of study of participants appeared to have contributed to their choice. From this research, we can infer that acting directly on emotion and intention strands is an important step towards the promotion of more environmentally responsible behaviours. Its contributions, contextualized on theoretical bases, rely on the environmental psychology field, with implications on the areas of marketing and consumer behaviour, making room for further research.